دراسة كمية ونوعية للطحالب القاعية في نهر الفرات عند مدينة الناصرية - الخفاجي باسم يوسف (University of Thi-Qar Journal of Science, 2014)
The current study included a conducted to identify the quantity and quality of Epipelic Algae in water of Euphrates River Al-Nasryia city. Samples were collected for the period from September , 2012 to August , 2013 from fourselected stations on the River. Epipelic algae were Diagnosed in the current study (158) species belonging to 63 Genera , were recorded and Bacillariophyceae are prevalent has stood at 87 species belonging to 21 genera, some studies four stations and above it (Nitzschia spp., Navicula spp ., synedra spp., Achnanthes spp., Cymbella spp.,) and next it cyanophyceae were recorded from it 36 species and 16 genera from study stations and diagnosed genera about it found in organic pollution water like Oscillatoria genera , were diagnosed species number for Chorophyceae 15 species and 11 genera in all study stations also study diagnosed 5 genera and 9 species from agae Euglenophyceae and were diagnosed species number from Chrysophyceae is 5 species and 4 genera diagnosed it from all study stations what fourth stations the study did not recoeded found on it , also the current study diagnosed 7 species and 6 genera belonging to Xanthophyceae Aseasonal and geographical variations were noted in the total number of Epipelic Algae by increases appeared during spring and the total number it ranged between (2.97-13.99)cellx /cm2.